2020
DOI: 10.3390/nu12061771
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxic Injury Differentially Regulates Brain Microvascular Gene Expression in Male Mice

Abstract: The Western diet (WD) and hyperlipidemia are risk factors for vascular disease, dementia, and cognitive impairment. However, the molecular mechanisms are poorly understood. This pilot study investigated the genomic pathways by which the WD and hyperlipidemia regulate gene expression in brain microvessels. Five-week-old C57BL/6J wild type (WT) control and low-density lipoprotein receptor deficient (LDL-R−/−) male mice were fed the WD for eight weeks. Differential gene expression, gene networks and pathways, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Interestingly, these transcripts were particularly enriched in the pathways regulating BBB permeability, neurofunction, inflammation, and neurodegeneration in the hippocampus. Recently, it has been shown that a western-type diet given to mice induces not only increased BBB permeability but also decreased cognitive function, 43 phenotypic changes found to be associated with significant changes in the expression of protein-coding as well as non-coding RNAs in hippocampal microvasculature of male 44 and female mice. 45 On the other hand, studies have suggested the capacity of EC to mitigate BBB dysfunction and protect from neurodegeneration via multi-omic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these transcripts were particularly enriched in the pathways regulating BBB permeability, neurofunction, inflammation, and neurodegeneration in the hippocampus. Recently, it has been shown that a western-type diet given to mice induces not only increased BBB permeability but also decreased cognitive function, 43 phenotypic changes found to be associated with significant changes in the expression of protein-coding as well as non-coding RNAs in hippocampal microvasculature of male 44 and female mice. 45 On the other hand, studies have suggested the capacity of EC to mitigate BBB dysfunction and protect from neurodegeneration via multi-omic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we characterized the effect of a high glycemic diet (HGD) on murine neurovascular function and cognition using hippocampal microvascular multiomics of mice exposed to high or low glycemic index diets. Utilizing similar techniques of large-scale transcriptome gene profiling, we have previously shown the effect of lipid stress and a Western diet (WD) on hippocampal microvascular injury and cognitive decline in male and female mice ApoE-/-and LDL-R-/-mice [8][9][10][11]. However, the molecular footprint of the glycemic component of the WD on the brain microvasculature, and whether and how the HGD may contribute to microvascular injury, was up to now unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has also become increasingly recognized that vasculature plays an important role in the development of dementias [7]. Our group has previously demonstrated the multi-omic and lipotoxic effect of a Western diet on the brain microvasculature and its negative consequences on cognitive function in male and female mice [8][9][10][11]. While there have been numerous mechanistic studies focusing on cognitive function with high-fat diets, few studies have explored the impact of high glycemia in the absence of high levels of dietary fat.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently thought that the dysregulation of lncRNAs promoted to malignant progression of cancer at the epigenetic, transcriptional, and posttranscriptional levels [20,21]. Some lines of evidences indicate that lncRNAs affect the transcriptional and epigenetic regulation of gene expression by acting as decoys for transcription factors, miRNA sponges, RNA interference, scaffolds for ribonucleoprotein complexes, recruiters of chromatin-modifying complexes, transcriptional regulation in cis or trans [22][23][24][25]. These ndings indicate that lncRNAs may be potential biomarkers for CRC.…”
Section: Introductionmentioning
confidence: 99%